0316 Almada Negreiros and Le Corbusier. Parallel Methodologies and Critical Reception - Simão Palmeirim (RIHA Journal)
The French-Swiss artist and architect Le Corbusier (1887–1965) created a system for architects and engineers to humanize the metric system, paving the way for a new form of architecture. The Portuguese artist José de Almada Negreiros (1893–1970) developed a multifaceted literary and artistic practice, progressively constructing a theory on the relation between art and geometry. There are parallels between these two artists in the way they devoted themselves to geometry and developed a theory with a universalistic approach that extended beyond their artistic production. Le Corbusier's international recognition has led to extensive research and dissemination of his works, whereas Almada's theoretical studies on geometry and art have only recently been the object of systematic research. Recently found documents in Almada's estate shed new light on the author's knowledge of Le Corbusier's Le Modulor, and his critical reception of such work. This paper reveals these documents and examines them in depth to identify both parallels and a structural, theoretical divergence between these authors.